Sosialisasi Pengelolaan Limbah Jeruk Menjadi Pupuk Organik Ramah Lingkungan di Desa Sidomulyo Kecamatan Semboro Kabupaten Jember - Huwaida, Hasna’; Marnata, Anggi; Rohman, Mutiur; Sulistyaningtyas, Nurul Hidayatullah (SEJAGAT : Jurnal Pengabdian Masyarakat, 2024)
In the agricultural sector, Semboro District is the main source of orange producers in Jember Regency. The bulk of the people that live in the Semboro District are farmers, and they created this. The issue in Semboro District's Sidomulyo Village is that farmers haven't been able to make the most of their leftover orange crop. The agricultural industry can handle the remaining oranges. It is possible for this industry to handle oranges that are unfit for consumption. KKN students in Sidomulyo Village are attempting to process orange waste by offering outreach in managing orange waste in an effort to turn it into an environmentally friendly organic fertilizer. To ensure sustainable management of the organic matter, farmers and the Thematic KKN Team 13 collaborate to maximize the use of organic fertilizer. This orange trash trial revealed that adding stale rice to orange waste MOL activates trichoderma, allowing the MOL to be utilized as a pesticide and enhance soil structure.